Navigating Challenges in Enhancing Pupils’ English Reading Comprehension through an Optimal Classroom Environment - Jerusalem, Bonifacio Tabianan; Orale, Ronald Libanan (Jurnal Pendidikan Progresif, 2023)
Creating an optimal classroom environment that fosters reading comprehension is crucial for maximizing students' potential. This qualitative phenomenological study aims to explore the perspectives, challenges, and coping strategies of teachers in creating such an environment. The findings revealed that teachers perceived an optimal classroom environment for enhancing reading comprehension to encompass a conducive learning environment, enriched learning experiences, and environmental factors. Additionally, the study highlights that teachers face challenges such as limited resources, including funding, materials, and technology, as well as classroom conditions and infrastructure. Moreover, student factors, including low interest in reading, health issues, and absenteeism, add complexity to the challenge. To address these challenges, teachers employ coping strategies like differentiated instruction, resource utilization, improvisation, and seeking parental involvement. To ensure a conducive learning environment for reading comprehension, it is crucial to address resource limitations, improve classroom conditions and infrastructure, recognize student factors and engagement, and foster parental support. Keywords: reading comprehension, resource limitation, optimum classroom environment, Phenomenology, teachers challengesDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202303